Performance and Carcass Characteristics of Japanese Quails Fed Diets Containing Wolffia Meal [Wolffia globosa (L). Wimm.] as a Protein Replacement for Soybean Meal - Chantiratikul, A.; Chantiratikul, P.; Sangdee, A.; Maneechote, U.; Bunchasak, C.; Chinrasri, O. (International Journal of Poultry Science, 2010)
The objectives of this study were to determine the effect of replacement of Crude Protein (CP) from Soybean Meal (SBM) with CP from Wolffia meal [Wolffia globosa (L). Wimm.] on performance and carcass quality in Japanese quails. Using Completely Randomize Design (CRD), two hundred eighty-eight quails were divided into four treatments. Each treatment consisted of six replicates and each replicate contained twelve quails. The dietary treatments were T1: control diet, T2, T3 and T4: CP from SBM was replaced by CP from Wolffia meal at 25, 50 and 75%, respectively. The results showed that the feed intake of quails significantly decreased (p0.05) feed efficiency, performance and carcass quality of quails. Skin pigmentation increased (p